A descriptive Analysis of Kurdish Political Discourse With Reference to Referendum Discourse - Srwa Faisal Azeez; Dyar Ali Kamal (Zanco Journal of Humanity Sciences)
This research is entitled "A descriptive Analysis of Kurdish Political Discourse, with Reference to Referendum Discourse". It is an attempt to descriptively analyze the referendum discourse. This analysis is one of the levels of critical discourse analysis method for analyzing discourse. In this research, Political discourse is taken because political discourse is a type of discourse in which the conflict between Authority and Society is crystalline, and this is the aim of critical discourse analysis. In the current research, with focusing on the main questions of descriptive analysis which have been developed by Fairclough as the strategy of discourse descriptive analysis, referendum discourse is descriptively analyzed. The research defines discourse as a social activity and relies on Fairclough's views in order to determine its theoretical framework.